How the Meaning of Home Changed since the Earthquake in 2015 in Kathmandu? (Rigvedic Himalaya, 2025)
This article takes shape from my research, which is grounded in themes from the anthropology of home. This field of study explores how people experience and give meaning to domestic space across different cultural, historical, and natural contexts. The aim I set was to study and to analyze the social and structural changes resulting from the earthquake that occurred in 2015 in Kathmandu, Nepal. The research question sought to analyze how this event influenced the perception of home, home-making practices, and the reconstruction of a sense of home among the affected individuals. It was considered the cultural dynamics, local responses, and the long-term impacts on the reconfiguration of housing identity. This is an ethnography I conducted between February and May of 2024. This fieldwork allowed me to collect direct testimonies through in-depth interviews and informal conversations with residents. The core of this article is to observe how the perception of home has changed in the aftermath of the 2015 earthquake. Through interviews who directly experience the event, it emerged that home is not only a physical structure, but is a space of emotional resilience and symbolic reconstruction.